2021
DOI: 10.1155/2021/5570356
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic of Candesartan and Music Therapy in Diabetic Retinopathy with Depression in Rats

Abstract: This study aimed to investigate the therapeutic effects of candesartan combined with music therapy on diabetic retinopathy with depression and to assess the molecular mechanisms. Associated animal model of diabetes mellitus and depression was established in rats. Pathological changes in the hippocampus were detected by haematoxylin eosin (H&E) staining. Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) was used to detect retinal cell apoptosis. Angiotensin II (Ang II) in peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Similarly, the AT1 receptor blocker telmisartan reduces depression in diabetic rats. Besides, ACEIs such as candesartan produce an antidepressant effect in animal model study 120 . The underlying mechanisms for the antidepressant effects of ARBs and ACEIs might be related to the upregulation of ACE2/Ang1‐7/MASR.…”
Section: Brian Ras and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the AT1 receptor blocker telmisartan reduces depression in diabetic rats. Besides, ACEIs such as candesartan produce an antidepressant effect in animal model study 120 . The underlying mechanisms for the antidepressant effects of ARBs and ACEIs might be related to the upregulation of ACE2/Ang1‐7/MASR.…”
Section: Brian Ras and Depressionmentioning
confidence: 99%
“…Besides, ACEIs such as candesartan produce an antidepressant effect in animal model study. 120 The underlying mechanisms for the antidepressant effects of ARBs and ACEIs might be related to the upregulation of ACE2/Ang1‐7/MASR. Different experimental studies have observed that overexpression of ACE2 and Ang1‐7 in transgenic rats promotes antidepressant and antianxiety effects that are reversed by using MASR antagonists.…”
Section: Brian Ras and Depressionmentioning
confidence: 99%
“…It has completed phase II trials (NCT00809562, NCT01437657) and is under further investigation by Hoffmann-La Roche for treatment-resistant and major depressive disorders. Candesartan is an angiotensin receptor blocker mainly used for hypertension treatment but has also been found to reverse depression-like symptoms in preclinical studies in the initial phase [ 140 , 141 ]. But, in clinical trials, it was withdrawn from phase I in the early phase (NCT04430959), and phase IV studies were terminated due to the adverse effects in treated patients (NCT01794455).…”
Section: Imidazole-based Drugs Under Clinical Trials Against Depressionmentioning
confidence: 99%
“…[22,23]. Classical music therapy has been practiced successfully on mice animal models for stress [24][25][26], diabetes mellitus [27], breast cancer [28], bone cancer [29], Alzheimer's disease [20], autism [30], and schizophrenia [31].…”
Section: Introductionmentioning
confidence: 99%